CD2‐Associated Protein Contributes to Hepatitis C, Virus Propagation and Steatosis by Disrupting Insulin Signaling. Issue 5 (27th October 2018) - Zhang, Huixia; Zhang, Chao; Tang, Hong; Gao, Shanshan; Sun, Fang; Yang, Yuan; Zhou, Weiping; Hu, Yu; Ke, Changshu; Wu, Yu; Ding, Zeyang; Guo, Lin; et al.
Abstract : Chronic hepatitis C virus (HCV) infection can result in steatosis, a condition displaying aberrant accumulation of neutral lipid vesicles, the component of lipid droplets (LDs), which are essential for HCV assembly. However, the interplay between HCV infection and steatosis remains unclear. Here, we show that HCV‐infected cells have higher levels of CD2‐associated protein (CD2AP), which plays two distinct, yet tightly linked, roles in HCV pathogenesis: Elevated CD2AP binds to nonstructural protein 5A (NS5A) and participates in the transport of NS5A to LDs to facilitate viral assembly; Up‐regulated CD2AP also interacts with casitas B‐lineage lymphoma (b) (Cbl/Cbl‐b) E3 ligases to degrade insulin receptor substrate 1 (IRS1), which, in turn, disrupts insulin signaling and increases LD accumulation through the IRS1/protein kinase B (Akt)/adenosine monophosphate‐activated protein kinase (AMPK)/hormone‐sensitive lipase (HSL) signaling axis to accommodate viral assembly. In the HCV‐infected mouse model, CD2AP expression is up‐regulated during the chronic infection stage and this up‐regulation correlates well with liver steatosis. Importantly, CD2AP up‐regulation was also detected in HCV‐infected human liver biopsies showing steatosis compared to non‐HCV‐infected controls. Conclusion: CD2AP is indicated as a protein up‐regulated by HCV infection, which, in turn, stimulates HCV propagation and steatosis by disrupting insulin signaling; targeting CD2AP may offer an opportunity for alleviating HCV infection and its associated liver pathology. (Hepatology 2018;XX:XXX‐XXX.)